The importance of the Whatsapp family group: an exploratory analysis. Issue 2 (21st March 2016) - Aharony, Noa; Gazit, Tali
Abstract : Purpose: – The purpose of this paper is to focus on WhatsApp, a mobile messaging service for smartphones that began in 2009. The study uses attachment theory, a social support perspective and one personality characteristic derived from the Big Five theory of personality ("openness to experience") and attempts to predict how these variables influence the importance of the WhatsApp family group. Design/methodology/approach: – Research was conducted in Israel during the first semester of the 2015 academic year and encompassed 191 undergraduate communication students. Researchers used six questionnaires to gather personal details, WhatsApp use, WhatsApp importance, attachment, openness to experience, and social support. Findings: – The findings confirm that the personality characteristic of openness to experience and social support significantly predict the importance of WhatsApp family group. Findings present a complex and ambiguous relationship between the attachment variables and the importance of WhatsApp family group. Originality/value: – The literature has not yet dealt with the issue of WhatsApp groups. Hence, the current study highlights associations between WhatsApp family group and attachment theory, the personality characteristic of openness to experience, social support, and family frequency use.